Effect of integrated case-based and problem-based learning on clinical thinking skills of assistant general practitioner trainees: a randomized controlled trial - Dingyuan Jiang; Danpei Huang; Hua Wan; Wuliang Fu; Weidong Shi; Jin Li; Huan Zou; Niannan Hou; Qing Li; Nani Li (BMC Medical Education)
Abstract Background Case-Based Learning (CBL) and Problem-Based Learning (PBL) are popular methods in medical education. However, we do not fully understand how they affect the clinical thinking skills of Assistant General Practitioner (AGP) trainees. This randomised controlled trial aimed to assess the effectiveness of combining CBL and PBL and compare their impact on the clinical thinking skills of AGP trainees with that of traditional lecture-based learning (LBL). Methods This randomised controlled trial involved 70 second-year AGP trainees who were randomly assigned to either the CBL-PBL group or the LBL group using a simple randomisation method. The CBL-PBL group engaged in a curriculum that integrated case-based and problem-based learning, whereas the LBL group followed a traditional lecture-based format, as described in the syllabus. To evaluate clinical thinking skills, the participants were assessed using the Clinical Thinking Skills Evaluation Scale (CTSES) and an assistant general practitioner’s professional knowledge test. In addition, this study analysed various factors that influence clinical thinking skills. Results Compared with the LBL group, the CBL-PBL group showed significantly improved performance in all domains assessed by the CTSES in post-course tests (p < 0.001). Specifically, the mean scores for critical, systematic, and evidence-based thinking showed notable improvement in the CBL-PBL group. Additionally, the scores on the professional knowledge test reflected a substantial increase in this group. Furthermore, multiple linear regression analysis showed that both CBL-PBL curriculum performance scores and number of weekly article readings significantly influenced the development of clinical thinking skills. Conclusion The CBL-PBL teaching method positively influenced the clinical thinking skills of assistant general practitioner trainees, with a positive correlation between these skills and course performance in the CBL-PBL curriculum. Trial registration Not applicable.